2021
DOI: 10.1681/asn.2020050717
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Derived miR-17∼92 Promotes Angiogenesis to Protect against Renal Ischemia-Reperfusion Injury

Abstract: BackgroundDamage to the renal microvasculature is a hallmark of renal ischemia-reperfusion injury (IRI)–mediated AKI. The miR-17∼92 miRNA cluster (encoding miR-17, -18a, -19a, -20a, -19b-1, and -92a-1) regulates angiogenesis in multiple settings, but no definitive role in renal endothelium during AKI pathogenesis has been established.MethodsAntibodies bound to magnetic beads were utilized to selectively enrich for renal endothelial cells from mice. Endothelial-specific miR-17∼92 knockout (miR-17∼92endo−/−) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In an experimental study on the role of microRNAs in kidney ischemia, Chiba et al indicated that the subjects presented high levels of microRNA-17, microRNA-18a, microRNA-19a, microRNA-20a, microRNA19b-1, and microRNA-92a-1 [ 180 ]. MicroRNA-24 was identified as a promoter of ischemic kidney injury, acting by stimulating the biological mechanisms of H2A-histone family and oxygenase 1 [ 181 ].…”
Section: Implications Of Genetic and Epigenetic Expression On Inflamm...mentioning
confidence: 99%
“…In an experimental study on the role of microRNAs in kidney ischemia, Chiba et al indicated that the subjects presented high levels of microRNA-17, microRNA-18a, microRNA-19a, microRNA-20a, microRNA19b-1, and microRNA-92a-1 [ 180 ]. MicroRNA-24 was identified as a promoter of ischemic kidney injury, acting by stimulating the biological mechanisms of H2A-histone family and oxygenase 1 [ 181 ].…”
Section: Implications Of Genetic and Epigenetic Expression On Inflamm...mentioning
confidence: 99%
“… 10 , 11 Accumulating studies have shown the capacity of endothelial miRNAs to regulate EC differentiation, homeostasis, and angiogenesis. 12 , 13 , 14 , 15 , 16 For example, miR-99b, miR-191a, and miR-181b are capable of potentiating EC differentiation from hESCs and improving hESC-EC-induced therapeutic neovascularization in vivo . 17 Other miRNAs mediating EC lineage specification include miR-21, miR-200c, miR-150, miR-6086/6087, miR-5739, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing studies revealed the role of miRNAs in renal I/R injury. For instance, endothelial-specific miR-17, -18a, -19a, -20a, -19b-1, and -92a-1 knockout promotes renal dysfunction following renal I/R injury through dysfunction of renal microvasculature [ 8 ]. Another study found that miR-218-5p promoted endothelial cell injury to accelerate renal injury [ 9 ].…”
Section: Introductionmentioning
confidence: 99%